Law in religious communities in the Roman period : the debate over Torah and Nomos in post-biblical Judaism and early Christianity - Richardson, Peter, 1935- (Studies in Christianity and Judaism, 1991)
The role and function of law in religious communities in the Roman period-especially in Judaism-has been a key issue among scholars in recent years. This thought-provoking work is the first full-scale attempt to write a historical assessment of the scholarly debate concerning this question, focussing on two closely related religious communities, Judaism and Christianity. By juxtaposing the two religions, a clearer understanding of the developments with respect to torah and nomos in Judaism and early Christianity emerges. This insightful work, placing emphasis on the major figures and both t.